2007
DOI: 10.1264/jsme2.22.11
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics of Sulphate-reducing Bacterial Compositions in Sediment along a Salinity Gradient in a UK Estuary

Abstract: The diversity of sulphate-reducing bacteria (SRB) was investigated in sediments along environmental gradients in the River Colne estuary, Essex, UK. DNA samples were collected from four sites; marine-dominated (Alresford Creek), brackish (the Hythe), predominantly freshwater (East Hill Bridge) and freshwater (the Weir) between September 2001 and May 2002. SRB community composition was assessed by PCR amplification, cloning and sequencing of part of the α subunit of dissimilatory sulphite reductase (dsrA) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…They showed that dsrAB sequences related to Desulfotomaculum were dominant in the freshwater SRB community and that δ-Proteobacterial dsrAB sequences dominated at a brackish site, suggesting that sulfate availability and salinity play a signifi cant role in structuring the SRB community in estuarine environments. In addition to sulfate content and salinity, organic carbon content is suggested to be responsible for the differences in the SRB communities in an UK estuary (Kondo et al, 2007). In the surface waters of Lake Suigetsu, cyanobacterial blooms of Microcystis and/or Anabaena occur during the summer season whereas a dinofl agellate dominates during the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that dsrAB sequences related to Desulfotomaculum were dominant in the freshwater SRB community and that δ-Proteobacterial dsrAB sequences dominated at a brackish site, suggesting that sulfate availability and salinity play a signifi cant role in structuring the SRB community in estuarine environments. In addition to sulfate content and salinity, organic carbon content is suggested to be responsible for the differences in the SRB communities in an UK estuary (Kondo et al, 2007). In the surface waters of Lake Suigetsu, cyanobacterial blooms of Microcystis and/or Anabaena occur during the summer season whereas a dinofl agellate dominates during the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the T75 libraries, members of the Deltaproteobacteria abounded (represented in the libraries by the genera Desulfobacteraceae, Desulfobulbaceae, Desulfuromonadales, Desulfobacterium). These genera encompass major sulphate reducing bacteria (SRB), which are anaerobic bacteria commonly found in freshwater and marine anoxic sediments (Rees and Patel, 2001;Klepac-Ceraj et al, 2004;Asami et al, 2005;Mussmann et al, 2005;Da Silva et al, 2007;Foti et al, 2007;Kjeldsen et al, 2007;Kondo et al, 2007;Miletto et al, 2007;Suzuki et al, 2007aSuzuki et al, , 2007b. SRB are frequently associated with the anaerobic hydrocarbon degradation process (PerezJimenez and Kerkhof, 2005;Kniemeyer et al, 2007;Miralles et al, 2007aMiralles et al, , 2007b.…”
Section: Minor Clustersmentioning
confidence: 99%
“…Other findings, such as the abundance of Alphaproteobacteria in estuarine and coastal environments 13) and the existence of Archaea in coastal waters 23) , have been revealed by the molecular analysis of prokaryotic microbial communities. The environmental control of bacterial assemblages 4,25) and the relationship between the aquatic environment and the distribution of functional bacterial groups 5,19) were also shown by molecular analyses of bacterial communities 15,18) . Among the methods of molecular analysis, the fluorescence in situ hybridization (FISH) technique, developed by DeLong et al 6) , provides quantitative information about bacterial community structure and the abundance of individual organisms in populations.…”
mentioning
confidence: 97%